THE CASE OF MENINGOENCEPHALITIS IN A CHILD FROM THE SOURCE TUBERCULOSIS INFECTION - L. A. Gusnisheva; O. S. Pozdeeva; O. G. Boyarinceva; M. V. Petrenko; S. V. Michaylov; E. A. Tulkina; O. V. Kuznetcova; O. V. Moiseeva; I. V. Phedorova (Детские инфекции (Москва))
In sectional clause the clinical case of a tubercular meningocephalitis at the child 6 years from the center drug resistant bacterial excretion is described. The analysis of the parents and risk factors of occurrence sectional astroprocessor of the shape of tuberculosis is given.